2020
DOI: 10.1186/s12933-020-01021-8
|View full text |Cite
|
Sign up to set email alerts
|

The sweet spot: fasting glucose, cardiovascular disease, and mortality in older adults with diabetes: a nationwide population-based study

Abstract: Background: Growing evidences shows that fasting glucose target should be different according to their health condition in older adults with diabetes. However, there are limited data regarding the relationship between fasting glucose level and health outcomes in Korean older people with diabetes. We aimed to examine the association of fasting glucose with mortality and cardiovascular events in Korean older adults with type 2 diabetes. Methods:From the Korean National Health Insurance System, 227,938 subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
3
11
3
Order By: Relevance
“…Our data indicate a primary role of diabetes and hypertension in the development of disability in a frail cohort of older adults. Furthermore, consistent with previous investigations [64,65], in our population we observed a robust impact of age (p < 0.001) and admission glycemia (p < 0.001), strongly suggesting that glycemic control is a goal to achieve for avoiding adverse outcomes in this class of patients. Indeed, hyperglycemia worsens a delicate balance in patients with multimorbidity such as frail elders [66][67][68].…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicate a primary role of diabetes and hypertension in the development of disability in a frail cohort of older adults. Furthermore, consistent with previous investigations [64,65], in our population we observed a robust impact of age (p < 0.001) and admission glycemia (p < 0.001), strongly suggesting that glycemic control is a goal to achieve for avoiding adverse outcomes in this class of patients. Indeed, hyperglycemia worsens a delicate balance in patients with multimorbidity such as frail elders [66][67][68].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a J-shaped association between FBG and the risk of MI. There are several studies showing the J-shaped relationship between FBG and CVD or mortality, independent of diabetes status [33,34]. A Chinese population-based prospective cohort study demonstrated that this association was evident in participants including untreated diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…While the association between MI or stroke with FBG levels was J-shaped, it did not show statistical significance, especially after adjustment for hypertension and dyslipidemia. An increased risk of cardiovascular events has been reported in older patients with diabetes and particularly high comorbidities among those with low FBG levels (<95 mg/dL) [ 18 ]. In the general Korean population, the HR of all-cause mortality was significantly higher in the low (<70 mg/dL) and high FBG ranges (≥126 mg/dL) than in the reference range (80 to 99 mg/dL) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%